JAVANESE IMPERATIVE SENTENCES IN THE DIALOGS OF 'ORA ATOS KAYA WATU' RADIO PLAY (KALIMAT IMPERATIF BAHASA JAWA DALAM DIALOG SANDIWARA RADIO 'ORA ATOS KAYA WATU') - Edysa Ariviani; Sumarlam Warsitadipura (Leksema: Jurnal Bahasa dan Sastra, 2019)
This research was aimed at describing the forms of Javanese imperative sentences of radio drama Ora Atos Kaya Watu (Not as Hard as a Stone) broadcasted by RRI Surakarta. The descriptions were based on the markers of each imperative sentence. As a type of descriptive-qualitative research, the data of this research were in the forms of morphemes, words, phrase, clauses, sentences gained from the the dialogues manuscripts of the drama. The data were collected by reading and note-taking which were then analyzed by using descrptive method. The result showed that the imperative sentences in the drama had two characteristics i.e.: ended with suffix -en, -a, -ana, or -na on their predicates and started with commands such as: ayo, sumonggo, and coba. Aside from that, there were two purposes intended by the imperative sentences as well, namely commanding for and forbidding from doing something. There were also found 9 types of meanings of the imperative sentences, i.e.: insisting, persuasions, suggestions, pleasing, prohibitions, commands, requests, asking, and recommendations.